Direct liquid extraction surface analysis mass spectrometry of cell wall lipids from mycobacteria: Salt additives for decreased spectral complexity. (29th October 2019) - Conner, Alexander N.; Jarvis, Jessie R.; Alderwick, Luke J.; Griffiths, Rian L.
Abstract : Rationale: Lipids are important mycobacterium cell wall constituents; changes are linked with drug resistance. Liquid extraction surface analysis (LESA) enables direct sampling in a highly sensitive manner. Here we describe protocols for the analysis of lipids from bacterial colonies. Lipids form various adducts, complicating spectra. Salt additives were investigated to circumvent this problem. Methods: Chloroform:methanol mixtures were studied for lipid extraction and analysis by LESA‐MS. The inclusion of (ESI‐compatible) acetate salts of sodium, potassium or lithium in the extraction solvent was investigated. Results: We report the detection of bacterial cell wall lipids from mycobacterial species using LESA for the first time. Sampling protocols were optimised for the use of volatile extraction solvents. The inclusion of acetate salt additives in the sampling solvent significantly reduces spectral complexity in comparison with no additives being used. Conclusions: LESA offers a sensitive technique for bacterial lipid phenotyping. The inclusion of an acetate salt in the sampling solvent drives adduct formation towards a specific adduct type and thus significantly reduces spectral complexity.